Doença renal crônica: uma avaliação do conhecimento dos médicos da atenção primária e dos médicos especialistas em nefrologia - BARROSO, Caroline Braga (2021)
Introduction: The Family Health Strategy is the main tool of Primary Health Care (PHC) since its implementation in the Unified Health System. In this context, the family health team has the role of making the first contact with the patient, approaching most situations and, when necessary, referring the patient to a reference service. The professional responsible for referring is the doctor. Thus, as chronic non-communicable diseases and, especially, chronic kidney disease (CKD) have a high prevalence in the general population, PHC, in the figure of the family doctor, has assumed a crucial role in the approach and control of these affections and their complications. Objective: to verify the level of knowledge of PHC physicians and nephrology specialists about CKD. Methods: this is a quantitative, cross-sectional, analytical, observational, noninterventionist study, carried out through primary data collection through the application of a written questionnaire. The survey was conducted from October 2020 to May 2021, and approached PHC physicians and nephrology specialists. Results and discussion: most physicians approached in this study were from PHC (82.1%) and, of these, 62.8% worked exclusively at the primary care level. Among specialists (17.9% of the total sample), 60% worked exclusively at the secondary care level. Regarding risk factors, staging, complementary exams, clinical management and treatment, both the PHC physicians and the specialists obtained good assertive responses (>50%). Regarding the diagnosis of CKD, the percentage of assertive responses from PHC physicians and specialist physicians was 41.8% and 80%, respectively. Adequate hemoglobin level for patients with CKD was correctly mentioned by only 22.7 and 40% of responses from APS physicians and specialist physicians. About laboratory changes that indicate suspending Angiotensin-Converting Enzyme Inhibitor, only 10.2% and 30.8% of the responses from the PHC physicians and specialists were assertive. Conclusion: Primary health care physicians and specialists demonstrated, in most responses, a good level of knowledge of CKD and no statistically significant difference was observed in most questions between the two groups.